Antibiotic Sensitivity in Complicated and Uncomplicated UTI in Potuakhali Medical College Hospital (Medicine Today, 2022)
Introduction: Urinary tract infection (UTI) is a common reason for attending hospital emergency departments (ED). A complicated urinary tract infection (UTI) is associated with structural or functional abnormalities of the genitourinary tract or presence of any underlying disease.Objective: To assess the antibiotic sensitivity in complicated and uncomplicated UTI.Materials and Methods: The study was carried out in the Department of Medicine and Department of Microbiology. The urine samples were collected from the OPDs (outpatients departments). These sample collection sites were chosen as they mostly covered the urban area of the city. The duration of the study was one and a half year from July 2018 to January 2020. The urine samples of 200 patients, comprised of 60 males and 140 females, who attended the outpatient departments (OPDs) of three hospitals and had clinical evidence of urinary tract infection, determined by treating physicians, were included in this study.Results: Most common isolated pathogen was Eschericia coli 170(85.0%) followed by staphylococcus aureus 40(20.0%) and Klebsiella (10%). Multiple organisms were found few cases. Regarding drug sensitivity it was observed that maximum sensitivity was to Amikacin 94.0% followed by Nitrofurantoin 92.0%, Levofloxacin 90.0%, Meropenam 88.0%, Amoxicillin+Clavulanate 70.0% and Cefixim 70.0%.Conclusion: Female patients were predominant most common isolated pathogen were Eschericia coli, staphylococcus aureus and Klebsiella. Amikacin, Nitrofurantoin, Levofloxacin, Meropenam and Amoxicillin+Clavulanate were more sensitive antibiotic.Medicine Today 2022 Vol.34(1): 70-74